The correlation between external apical root resorption and electric pulp test responses: a prospective clinical trial - Farnaz YOUNESSIAN; Mohammad BEHNAZ; Mohammadreza BADIEE; Kazem DALAIE; Arezou SARIKHANI; Shiva SHEKARIAN; Shahab KAVOUSINEJAD; Asghar EBADIFAR (Dental Press Editora, 2021)
ABSTRACT Objective: The current study investigated the correlation between pulpal sensitivity to the electric pulp tester (EPT) and external apical root resorption (EARR) in four types of maxillary anterior teeth of fixed orthodontic treatment patients. Methods: In this prospective cohort study, 232 anterior teeth of 58 patients (mean age 18.96 ± 6.13 years) treated with fixed orthodontic treatment were examined. The EPT readings were recorded at twelve time points immediately before archwire insertion. Root resorption of four maxillary incisors were measured by means of parallel periapical radiographs at three time intervals (six months interval from the start) through design-to-purpose software to optimize data collection. A multiple linear regression model and Pearson correlation coefficient were used to assess the association of EPT values and observed EARR (p< 0.05). Results: The highest level of EPT measurement was recorded at initial visit, and then there was a decreasing trend in EPT level during treatment for the next six and twelve months. There was another increasing trend after six months till the finishing time of the treatment. There was a significant correlation between changes in root length and time of recording the root length (p< 0.001). There was significant positive correlation between changes in EPT level and amount of observed root resorption (p< 0.001). Conclusion: The relative decrease in electric pulp test level could be a diagnostic sign of root resorption during orthodontic treatment. Further studies with longer follow up are needed to confirm the current results.